Modernization and Transformation Perception as well as Practice Dui Pappenre: Challenges for Human Resource Management in Society Bugis Contemporary - Abdullah, Ruslan; Hartati, Hartati; Dinsar, Arfandi; Modding, Basri (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2024)
This study examines the transformation of Dui Pappenre's perceptions and practices in the context of the modernization of contemporary Bugis society and its implications for human resource (HR) management. Using a qualitative method with a case study approach, this study explores how the Dui Pappenre tradition affects the productivity, career development, and welfare of the young generation of Bugis in the world of work. The study results show that the financial stress caused by Dui Pappenre can reduce work motivation, productivity, and work quality, as well as affect career decisions and stress levels. To address these challenges, a comprehensive approach to HR management is needed, including financial aid programs, flexible policies, and creating an inclusive organizational culture. The study concludes that integrating Dui Pappenre's understanding of cultural practices into HR policies can help individuals manage financial challenges while maintaining productivity and well-being, as well as creating a more harmonious and effective work environment.